Risk Factors for Latent Tuberculosis Infection (LTBI) Among Household Contacts of TB Patients: A Systematic Review - Jihan Fadilah Faiz; Ella Nurlaella Hadi (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Latent Tuberculosis Infection (LTBI) is a condition in which an individual carries the TB bacteria without showing symptoms of active disease. An estimated 2.3 billion people globally are infected with LTBI, with household contacts of TB patients identified as a high-risk group. This systematic review aims to identify risk factors for LTBI among household contacts of TB patients. We conducted a literature search using Science Direct, PubMed, and Google Scholar, covering the period from 2019 to 2024. Inclusion criteria included studies on LTBI risk factors among household contacts of TB patients, written in English or Indonesian, research articles, and participants who lived with an active TB patient for at least one night and/or had frequent interactions with the patient within three months prior to TB treatment, Interferon-Gamma Release Assays (IGRA) or Tuberculin Skin Test (TST) tests were required. We evaluated article quality using the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist. Nine articles were included. LTBI risk factors among household contacts of TB patients include increasing age, male, occupation type (farmers or laborers or fishermen), duration of employment for more than 10 years, duration of working hours for more than 8 hours per day, contact with TB patients, sharing a bedroom with TB patients, bedroom density, overweight, and owning pets. Government, healthcare workers, and the society particularly household contacts of TB patients, must understand these LTBI risks to prevent further transmission and support the 2030 TB elimination program.